No rasto da guerra - Iria Gonçalves (Medievalista)
At the end of the 14th century Lisbon experienced days of great anxiety and suffering, due to the wars in which Portugal was involved with Castile, exacerbated by the fact that its already preeminent place in the realm. Convinced that the misfortunes that befell them were divine punishment for the sins committed, the "honourable" citizens of Lisbon listed the most nefarious of those sins, proscribed and punished with pecuniary penalties and a great series of religious ceremonies was planned in their favour. The outcome of the battle of Aljubarrota, proving that God had heard their prayers, led them, as sign of gratitude, to increased the actions of praise previously determined with promises of amendment.